On the asymmetric advantages of cyberwarfare. Western literature and the Chinese journal Guofang Keji. Issue 2 (23rd February 2020) - Dossi, Simone
ABSTRACT: An issue that has been widely debated in the West is whether cyberwarfare gives militarily weaker actors asymmetric advantages. Is cyberwarfare a weapon of the weak? Or does it rather multiply the advantages enjoyed by militarily superior actors? These questions have major implications for China, which – as a rising power – must face stronger and weaker opponents at the same time. Based on an analysis of the Chinese journal Guofang Keji, this article investigates how China's strategic community theorises advantage and disadvantage in the cyber domain and how this differs from Western perspectives on cyberwarfare.